The relationship between supervisory support, learning goal orientation, proactive personality and career adaptability among engineers at Texas Instruments Electronics Malaysia Sdn. Bhd. / Siti Hawa Mazlan - Mazlan, Siti Hawa (Faculty of Business and Management, 2020)
Career adaptability refers to the flexible attribute of individuals toward their career endeavour in the face of volatile circumstances. In striving towards a high-income nation status by 2020, the Malaysia’s manufacturing sector remains a core sector for sustainable growth under the 11th Malaysia Plan. The manufacturing sector has played a vital role in the economic transformation as Malaysia continue to attract huge investments in the manufacturing sector despite a challenging economic environment due to its highly-diversified economy, strong manufacturing foundation, developed infrastructure and connectivity, proactive Government policies and hardworking workforce. As the technology continually improve in Malaysia, every employee needed to be equipped with advance skills and knowledge especially among engineers. The improvement in technology also urges employees to be adaptable in any changes that occur in their career. Hence, this study is to assess the relationship between supervisory supports, learning goal orientation, proactive personality and career adaptability among engineers at Texas Instruments Electronics Malaysia Sdn. Bhd. (TIEM). Data was obtained from 118 questionnaires for these researches are from among engineers at TIEM. The result analysed with Statistical Package for the Social Science (SPSS) indicates a positive and significant correlation between supervisory support, learning goal orientation, proactive personality and career adaptability among engineers with supervisory support having the strongest significant relationship with career adaptability. Thus, it is noteworthy to mention that supervisor or employer should have taken proactive action in making sure the subordinates are ready to adapt for any changes in their career.